Analysis of Standard Time Determinationin Order to Increase U-Ditch Production Results at PT. The Charm of Arnos Beton Gresik - Ramadhani, Imam; Rusindiyanto, Rusindiyanto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to determine the standard time required in one work cycle of U-DITCH concrete production so that it can meet and increase production targets and identify things that can be improved to increase operational efficiency and productivity. This study uses a work sampling method with calculations of cycle time, normal time, and standard time. Sampling of work using random numbers and field observations was carried out for 14 days. Based on the data processing that has been done, it can be seen that it is 73%, as well as a cycle time of 8.21 minutes/ Unit and normal time with an adjustment level of 1.5933 gets a time of 13.08 minutes/ Unit. The number of productive minutes is 5,518.8 minutes with the number of outputs that have been completed for 14 days of 672 Units. The standard time with a slack factor of 46% gets a result of 683.31 hours/ Unit and a standard output of 73 Units is obtained for 1 day.